A retrospective analysis of 509 consecutive interscalene catheter insertions for ambulatory surgery. (10th September 2014) - Marhofer, P.; Anderl, W.; Heuberer, P.; Fritz, M.; Kimberger, O.; Marhofer, D.; Klug, W.; Blasl, J.
Summary Effective pain therapy after shoulder surgery is the main prerequisite for safe management in an ambulatory setting. We evaluated adverse events and hospital re‐admission using a database of 509 interscalene catheters inserted during ambulatory shoulder surgery. Adverse events were recorded for 34 (6.7%) patients (9 (1.8%) catheter dislocations diagnosed in the recovery room, 9 (1.8%) catheter dislocations at home with pain, 2 (0.4%) pain without catheter dislocation, 1 (0.2%) 'secondary' pneumothorax without intervention and 13 (2.6%) other). Twelve (2.4%) patients were re‐admitted to hospital (8 (1.6%) for pain, 2 (0.4%) for dyspnoea and 2 (0.4%) for nausea and vomiting), 9 of whom had rotator cuff repair. A well‐organised infrastructure, optimally trained medical professionals and appropriate patient selection are the main prerequisites for the safe, effective implementation of ambulatory interscalene catheters in routine clinical practice.